ANALISIS RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA PADA PT. PERUSAHAAN LISTRIK NEGARA (PERSERO) - Lisa (JURNAL AKUNTANSI DAN MANAJEMEN MADANI, 2025)
This study aims to analyze the impact of financial ratios on profit growth at PT Perusahaan Listrik Negara (Persero). The research employs a quantitative descriptive approach, using balance sheet and income statement data from 2012 to 2023 as the sample. The analysis results indicate that all variabel meet classical assumption test, including normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. The multiple linear regression analysis using the ttest (partial test) show that Current Ratio (CR), Debt Ratio (DR) and Total Assets Turnover (TATO) do not affect profit growth, while Net Profit Margin (NPM) has a significant impact on profit growth. Furthermore, the F-test (simultaneous test) confirms that Current Ratio (CR), Debt Ratio (DR), Total Assets Turnover (TATO) and Net Profit Margin (NPM) collectively influence profit growth.